Update on the role of eslicarbazepine acetate in the treatment of partial-onset epilepsy - Tambucci R; Basti C; Maresca M; Coppola G; Verrotti A (Neuropsychiatric Disease and Treatment)
Renato Tambucci,1 Claudia Basti,1 Maria Maresca,1 Giangennaro Coppola,2 Alberto Verrotti11Department of Pediatrics, University of L’Aquila, L’Aquila, Italy; 2Child and Adolescent Neuropsychiatry Unit, University of Salerno, Salerno, ItalyAbstract: Eslicarbazepine acetate (ESL) is a once daily new third generation antiepileptic drug that shares the basic chemical structure of carbamazepine and oxcarbazepine – a dibenzazepine nucleus with the 5-carboxamide substituent, but is structurally different at the 10,11-position. ESL is a pro-drug metabolized to its major active metabolite eslicarbazepine. Despite the fact that the exact mechanism of action has not been fully elucidated, it is thought to involve inhibition of voltage-gated sodium channels (VGSC). ESL inhibits sodium currents in a voltage-dependent way by an interaction predominantly with the inactivated state of the VGSC, thus selectively reducing the activity of rapidly firing (epileptic) neurons. ESL reduces VGSC availability through enhancement of slow inactivation. In Phase III studies, adjunctive therapy with ESL 800 or 1,200 mg/day leads to a significant decrease in the seizure frequency in adults with refractory partial onset epilepsy. Based on these results, ESL has been approved in Europe (by the European Medicines Agency) and in the United States (by the US Food and Drug Administration) as add-on therapy. Data on efficacy and safety have been confirmed by 1-year extension and real life observational studies. Recently, based on results from two randomized, double-blind, historical control Phase III trials, ESL received US Food and Drug Administration approval also as a monotherapy for patients with partial onset epilepsy. In the pediatric setting, encouraging results have been obtained suggesting its potential role in the management of epileptic children. Overall ESL was generally well tolerated. The most common adverse events were dizziness, somnolence, headache, nausea, diplopia, and vomiting. Adverse events can be minimized by appropriate titration. In conclusion, ESL seems to overcome some drawbacks of the previous antiepileptic drugs, suggesting a major role of ESL in the management of focal onset epilepsy for both new onset and refractory cases, either as monotherapy or as adjunctive treatment.Keywords: eslicarbazepine, partial-onset epilepsy, antiepileptic drugs, refractory epilepsy